Physiological and pathological regulation of feto/placento/maternal leptin expression. (May 2001) - Linnemann, K.; Malek, A.; Schneider, H.; Fusch, C.
Abstract : There is clear evidence of placental leptin production, as shown recently in trophoblast cultures and by dual in vitro placenta perfusion (median production of 225 pg/min per g of tissue; 98.4% released into the maternal and 1.6% into the fetal circulation). However, the physiological impact for the mother and the fetus is unclear. The classical role of leptin is to provide information about energy stores to the central nervous system, and to reduce appetite if the energy stores are full. In pregnancy, maternal plasma leptin concentrations are elevated, and lack the well established correlation with body fat energy stores that is observed in non-pregnant women, indicating an alternative function for leptin during pregnancy and fetal development. Maternal and fetal plasma leptin levels are dysregulated in pathological conditions such as gestational diabetes, pre-eclampsia and intra-uterine growth retardation, representing an effect or a cause of disturbances in the feto/placento/maternal unit.